SQUEEZING PHENOMENON HANDLING ON WATER TUNNEL AT MANIKIN DAM IN KUPANG BY USING GROUTING - Three Putra Sitanggang, Sebagus
Squeezing is a kind of major deformation which relies on time that occurs around the tunnel, and can be associated with creep caused by exceeding a limiting shear stress. The potential occurrence of squeezing can be raised by several factors such as the decreasing of rock mass strength specifically the deformation modulus and the rise of K value which shows that the tunnel’s condition is not hydrostatic. The problem of squeezing phenomena that occurs on the water tunnel’s wall of Manikin Dam can be overcome with grouting which is a pre-support method. Grouting is a reinforcement/strengthening method which method of application is by injecting a mix of cement and water into the rocks around the tunnel with certain pressure, later on after a period of time the mixed fluid will be physically and chemically solid. In general, the installation of grouting’s width is greater than the tunnel’s plastic zone when supports have not yet been installed. Analysis result shows that there’s a decline in displacement total value in the application of squeezing handling with grouting method. Handling with grouting was carried out at E values of 230 MPa, 100 MPa, and 80 MPa, initially the tunnel had a displacement value of 21 cm, 45cm, and 55 cm, after grouting the tunnel experienced a decrease in displacement to 7.1 cm, 12 cm and 13.7 cm. Therefore, grouting is one of the most effective methods of handling the squeezing phenomenon in resisting the deformation that occurs around the water tunnel of Manikin Dam.